2008
DOI: 10.1086/590006
|View full text |Cite
|
Sign up to set email alerts
|

Low Serum Mannose‐Binding Lectin Level Increases the Risk of Death due to Pneumococcal Infection

Abstract: We defined a serum level for MBL deficiency that can be used with confidence in future studies of MBL disease associations. The risk of death was increased among MBL-deficient patients with severe pneumococcal infection, highlighting the pathogenic significance of this innate immune defence protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
155
0
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(174 citation statements)
references
References 42 publications
12
155
0
7
Order By: Relevance
“…Generally, with age, there is a decreasing trend in serum MBL concentrations. This finding is also in line with previous studies which show that the frequency of low serum MBL level (using the cut-off , 500 ng/ml) is ∼25% in the general population (12,20).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Generally, with age, there is a decreasing trend in serum MBL concentrations. This finding is also in line with previous studies which show that the frequency of low serum MBL level (using the cut-off , 500 ng/ml) is ∼25% in the general population (12,20).…”
Section: Discussionsupporting
confidence: 93%
“…Mutant variants are unable to properly form the MBL molecule multimer; thus, the amount of functional MBL in blood and tissues decreases (10,11). MBL pathway deficiency is considered the most common congenital immunodeficiency of humans; it affects approximately one fourth of the general population (12,13).…”
Section: Yme Borreliosis (Lb) Is the Most Common Pathogenic Tick-mentioning
confidence: 99%
“…In a recent analysis of a large patient cohort it was shown that MBL serum levels can reliably indicate genetic MBL deficiency. 16 The ELISA we used strongly correlates with both the functional activity of the lectin pathway and the presence of low-producing MBL2 genotypes. 17 Furthermore, ELISA measurements of MBL allow an estimation of in vivo MBL status that may be caused by gene polymorphisms including, but not restricted to, the six well-known polymorphisms in the promoter and the first exon.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the association between genetic variations in MBL2 , and to a lesser extent FCN2 , and susceptibility to disease have been the subject of various studies 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31. An association between MBL2 polymorphisms and clinical outcome has been described in children with recurrent infections22 and in adult patients with meningococcal sepsis 17…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the role of MBL2 polymorphisms in invasive pneumococcal disease25, 27, 30, 31 and CAP23, 24 has been studied but with conflicting results. In addition, several studies show that MBL dysfunction is associated with a worse clinical outcome in patients with CAP, sepsis and bacteraemia 21, 24, 26. Only one study investigated the role of FCN2 polymorphisms in pneumococcal disease and showed no apparent relation 19…”
Section: Introductionmentioning
confidence: 99%